The Role Of Traditions In The Prevention And Management Of Chronic Energu Deficiency In Pregnant Woman - Teuku Nih Farisni; Dewi Farida; Maulida Saari (JKA, 2024)
Chronic energy deficiency (CED) during pregnancy is still a significant public health concern, especially in resource-limited areas. This study examines the role of traditional practices and institutions in preventing and managing CED among pregnant women. Traditional practices, such as culturally ingrained dietary habits, community-based support systems, and health rituals, make valuable contributions to maternal health by offering localized and culturally relevant solutions. These practices often complement modern health interventions by addressing the nutritional and social needs specific to the community context. The study highlights how integrating traditional knowledge with contemporary healthcare strategies can enhance the effectiveness of CED management and prevention. By fostering collaboration between traditional practitioners and modern healthcare providers, communities can develop comprehensive and culturally sensitive approaches to improving maternal health outcomes. This approach not only respects cultural traditions but also bridges the gap between traditional and modern health practices.